Analisis Kualitas Kehidupan Kerja dan Spiritualitas di Tempat Kerja terhadap Kinerja Karyawan di Lembaga Pendidikan Nurul ‘Ula Kota Kediri - Zulfiana, Nabilah; Arisyahidin, Arisyahidin; Mulyaningtiyas, Ratna Dewi (Otonomi, 2025)
The purpose of this research is to know the of quality of work life, to know the workplace spirituality, to know the employee performance, and the effect of quality of work life and workplace spirituality to work employee performance at Nurul ‘Ula Kota Kediri Educational Institution Kediri City. The population of this study consists of all employees at the institution, totaling 40 employees, with a saturated sample of 40 employees. The research employs a quantitative method, with data collected from respondents using questionnaires. After data collection, the data was processed using SPSS and analyzed using multiple linear regression. The result indicated that the quality of work life influence employee performance, however the effect is in the opposite direction or negatively correlated, workplace spirituality has a positive influence on employee performance, quality of work life and workplace spirituality have a simultaneous influence on employee performance at Nurul ‘Ula Kota Kediri Educational Institution. However, while quality of work life has an influence on employee performance at the institution.